2013
DOI: 10.1371/journal.pbio.1001517
|View full text |Cite
|
Sign up to set email alerts
|

The Case of the Missing Mechanism: How Does Temperature Influence Seasonal Timing in Endotherms?

Abstract: How temperature affects the timing of life cycles in warm-blooded organisms remains a mystery but must be addressed in order to predict the future consequences of global warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 86 publications
2
110
1
Order By: Relevance
“…These include food [53,54], social interactions [55], weather conditions [8] and especially ambient temperature [56]. In hibernating mammals, changes in temperature can advance phases within circannual rhythms.…”
Section: (D) Temperature and Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include food [53,54], social interactions [55], weather conditions [8] and especially ambient temperature [56]. In hibernating mammals, changes in temperature can advance phases within circannual rhythms.…”
Section: (D) Temperature and Other Factorsmentioning
confidence: 99%
“…Based on neuroanatomical evidence in the prairie vole, Kriegsfeld et al [64] suggest that lower temperatures may inhibit the release of GnRH by neurons located in a brain area that also contains temperature-sensitive neurons. Together, these results suggest that environmental temperature may act on both the input signal and the target neurons of the photoperiodic timing mechanism, but the precise nature of such temperature effects remains elusive [56].…”
Section: (D) Temperature and Other Factorsmentioning
confidence: 99%
“…More recently, De Jong and colleagues experimentally altered light levels in eight forests across the Netherlands and showed a 5 day advanced in laying date of great tits (De Jong et al 2015 ). The temporal discrepancy found between the effects of light at night on reproductive physiology and laying date suggests that while reproductive physiology of temperate avian species is mostly modulated by light (Dawson et al 2001 ), and thus light pollution can have a stronger effect on it, laying date is a complex life history decision that is regulated not only by photoperiod, but also by factors that reflect more the current environmental conditions, such as temperature and food abundance (Caro et al 2013 ). A recent captive study on the relationship between gonadal growth and egg laying date has shown very weak correlation between the two variables, highlighting that these are independent mechanisms that can be differentially affected by artificial lights (Schaper et al 2012 ).…”
Section: Light Pollution and Annual Cyclesmentioning
confidence: 99%
“…While photoperiod is used as proximate cue, birds rely on other external information to fine-tune the ultimate breeding decisions, e.g., laying the first egg of their clutch. Among the most important of these supplementary cues, food availability, temperature and social cues are the most understood [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ambient temperature and food availability have also been suggested to affect reproductive timing [16]. In the last 15 years the role of temperature for avian seasonal timing has become a major focus of ecology as attention has been drawn on the relationship between global warming and population decline of avian species [17], but the physiological mechanisms through which temperature affects timing of reproduction in birds are only partially understood [7,18]. Natural variation in food availability, as well as food supplementation experiments, has been long known to affect timing of breeding: in general, the more abundant the food availability is in a certain year, the earlier birds tend to lay their eggs [8,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%